Analisis Pengembangan Sektor Pariwisata Bukit Tungku Wiri Doyo dalam Upaya Meningkatkan Ekonomi Lokal di Kabupaten Jayapura - Grace Rosalia Meraudje; Yundy Hafizrianda; Risky Novan Ngutra (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2023)
This study aims to analyze the development of the Bukit Tungku Wiri Doyo tourism sector in improving the local economy in Jayapura Regency. The research employs a qualitative descriptive method, with data collected through interviews and documentation. The analysis applies the Tourism Area Life Cycle (TLC) approach and SWOT analysis to identify internal and external factors. The results indicate that the tourism site has significant natural potential; however, its management remains suboptimal due to limited facilities and inadequate management systems. Recommended development strategies include improving infrastructure, strengthening management, and enhancing the involvement of government and local communities. Optimal development is expected to increase tourist visits and improve local community income. Keywords: tourism, local economy, SWOT, destination development